ANATOMICAL INVESTIGATION OF FIVE GENERA THE LEAST-KNOWN TIMBER OF APOCYNACEAE AND THEIR POTENTIAL UTILIZATION - Sari Delviana Marbun; Vidya Fatimah Astutiputri; Ratih Damayanti; Hadisunarso; Deazy Rachmi Trisatya; Djarwanto; Listya Mustika Dewi; Raden Gunawan Hadi Rahmanto; Dyah Ayu Agustiningrum; Rohmah Pari; Imran Arra’d Sofianto; Yunita Lisnawati; Titi Kalima; Sona Suhartana; Setiowati; Krisdianto; Marfuah Wardhani; Agus Ismanto; Yuniawati; Agung Wahyu Nugroho; Sri Utami; Wahyu Dwianto; Widya Fitriasari; Adik Bahanawan; Danang Sudarwako Adi; Sarah Augustina; Hengki Siahaan (APTKLHI, 2023)
Doubtlessly, wood identification is critically important for a number of sectors, including government organizations, the wooden-based industry, museums, law enforcement, and scientists working in the fields of botany, ecology, forestry, and wood technology. Unfortunately, most wood species listed as “the least-known species” lack essential knowledge or even their anatomical feature and basic properties to promote their usage. This research aimed to investigate the anatomical characteristics and fiber quality of the least-known timber species of Apocynaceae family, which are authentic wood collection from Xylarium Bogoriense, namely , Ervatamia. sphaerocarpa, E. aurantiaca, Kopsia flavida, Lepiniopsis ternatensis, Plumeria acuminata, P. rubra, and Voacanga foetida. Wood samples have indistinct growth ring boundaries, diffuse-porous vessels in diagonal and/or radial pattern, vessels in radial multiples of 4 or more cells, simple perforation plate, alternate intervessel pits; distinct borders of vessel-ray pits, similar with those of intervessel pits in size and shape throughout the ray cell, and septate fibers with simple pits to minutely bordered pits which are common in radial and tangential walls. Based on the fiber length and the derived values of fiber dimension, some species are classified into Quality Class II and III, and the rest of them are classified into Quality Class II or III for pulp and paper manufacturing. Based on general characteristics, commonly Apocynaceae can be used as handicrafts raw material. Based on the fiber quality, some species which are classified into Quality Class II, are predicted to have potential as pulp and paper material with medium quality.